Enduring myths that inhibit school turnaround - Meyers, Coby V.; Darwin, Marlene (Contemporary perspectives on school turnaround and reform., 2017)
The concept of school turnaround--rapidly improving schools and increasing student achievement outcomes in a short period of time--has become politicized despite the relative newness of the idea. Unprecedented funding levels for school improvement combined with few examples of schools substantially increasing student achievement outcomes has resulted in doubt about whether or not turnaround is achievable. Skeptics have enumerated a number of reasons to abandon school turnaround at this early juncture. This book is the first in a new series on school turnaround and reform intended to spur ongoing dialogue among and between researchers, policymakers, and practitioners on improving the lowest-performing schools and the systems in which they operate. The "turnaround challenge" remains salient regardless of what we call it. We must improve the nation's lowest-performing schools for many moral, social, and economic reasons.In this first book, education researchers and scholars have identified a number of myths that have inhibited our ability to successfully turn schools around. Our intention is not to suggest that if these myths are addressed school turnaround will always be achieved. Business and other literatures outside of education make it clear that turnaround is, at best, difficult work. However, for a number of reasons, we in education have developed policies and practices that are often antithetical to turnaround. Indeed, we are making already challenging work harder. The myths identified in this book suggest that we still struggle to define or understand what we mean by turnaround or how best, or even adequately, measure whether it has been achieved. Moreover, it is clear that there are a number of factors limiting how effectively we structure and support low-performing schools both systemically and locally. And we have done a rather poor job of effectively leveraging human resources to raise student achievement and improve organizational outcomes.We anticipate this book having wide appeal for researchers, policymakers, and practitioners in consideration of how to support these schools taking into account context, root causes of low-performance, and the complex work to ensure their opportunity to be successful. Too frequently we have expected these schools to turn themselves around while failing to assist them with the vision and supports to realize meaningful, lasting organizational change. The myths identified and debunked in this book potentially illustrate a way forward.